(untitled) (Northern International Medical College Journal, 2020)
Central diabetes insipidus (CDI) occur due to deficiency of vasopressin which is synthesized in supraoptic and paraventricular nuclei of hypothalamus and stored in posterior pituitary. There are many causes of CDI among them histiocytosis X or lymphohistiocytosis (LCH) is a rare cause. Here we are reporting a 2 years old boy with histiocytosis-Xor presented with CDI. The boy presented with polyuria and polydipsia, low urine specific gravity and osmolality with normal blood sugar and osmolality. Positive response to water deprivation test followed by oral DDAVP establish the diagnosis of CDI. X-Ray skull showed osteolytic punched out lesion and T1 weighted MRI of brain showed thickening of pituitary stalk with absence of bright signal of posterior pituitary. Trephine biopsy showed bone marrow was infiltrated by many eosinophil, some macrophage, lymphocyte and plasma cells. On the basis of all these diagnosis was made as CDI due to histiocytosis-X. Due to hypothalamic- pituitary axis infiltration CDI may be the earliest manifestation of LCH, even before it is diagnosed. Therefore, for diagnostic workup of CDI, LCH should be considered. Northern International Medical College Journal Vol. 11 No. 1 July 2019, Page 432-434